Modeling of traction-energy processes in the electric traction system (Transport systems and technologies, 2020)
The paper presents a mathematical model of a subway electric traction system, taking into account the variation of the parameters of the system objects according to their cross-connections, spatial orientation and subjective factors. The peculiarities of mathematical modeling of the subway traction network with decentralized bilateral power supply of the contact rail from two traction substations are outlined, its substitution scheme is shown. A mathematical model of the subway traction network with decentralized two-sided feed of the contact rail from two traction substations has been developed. An approach to mathematical modeling of electric traction rolling stock as an object of formation of energy exchange processes in an electric traction system is proposed. The mathematical model is based on the presentation of its traction and braking characteristics in the form of tabular functions using interpolation to find the intermediate values of traction and braking force, as a function of not only the linear speed of movement but also other values. To confirm the correctness of the proposed mathematical fashion for the study of traction and energy processes in the system of electric traction, its simulation was performed. The simulation model was developed and simulated using Matlab software using the Simulink simulation graphical environment. As a traction moving unit was considered a subway car model 81-7036, was formed a conditional profile of movement with characteristic elements for the subway, namely the profile of movement with three interstation sections of equal length (1700 m) with different elements (platform, slope, lift). The result was a comparative evaluation of the simulation results obtained with the data package obtained during the operation of the real object and the correspondence of the obtained results with the passport data of the real object and the experimental data of his work. Attention is drawn to the need to take into account the variation of the electrical parameters of the traction network during rolling stock rolling stock.
Keywords: mathematical model, traction network, space-oriented scheme, electric trains, substitution scheme